How director remuneration impacts firm performance: an empirical analysis of executive director remuneration in Pakistan - azlam, ejaz; Haron, Razali; Tahir, Muhammad Naveed (Borsa Istanbul Anonim Sirketi, 2019)
This study empirically investigates the interrelationship between pay and performance of CEOs/board of directors in an emerging market, Pakistan. The study uses GMM approach to account for the problem of potential endogeneity and unobserved heterogeneity that arises due to the potential reverse causality (pay and performance) for a sample of non-financial firms listed in the KSE over the period of 2009e2016. This study provides evidence that pays-performance framework supports the agency theory whereby CEOs/board of directors are compensated for their prior level of market-based performance. In addition, pay performance framework weakly support the notion of the steward/tournament theory where the CEOs/board directors pay sensitivity weakly enhanced the firm performance. Thus, CEOs/board director's remuneration is highly persistent and takes time to adjust to long-run equilibrium.